The Role of Intermittent Fasting and Dieting on Cognition in Adult Population: A Systematic Review of the Randomized Controlled Trials - Senderovich, Helen; Farahneh, Othman; Waicus, Sarah (Medical principles and practice, 2023)
Objective: A healthy diet is a modifiable risk factor that may impact cognition. A unique type of diet may include intermittent fasting (IF), an eating pattern in which individuals go extended periods with little or no meal intake, intervening with periods of normal food intake. IF has multiple health benefits including maintenance of blood glucose levels, reduction of insulin levels, depletion or reduction of glycogen stores, mobilization of fatty acids, and generation of ketones. IF has shown neuroprotective effects as it may lead to increased neurogenesis in the hippocampus, which may contribute to cognitive resilience. Diets including IF were examined as lifestyle modifications in the prevention and management of cognitive decline. Methods: A systematic literature search was conducted for randomized controlled trials (RCTs) which assessed the effect of dieting on cognitive functions in adults. Results: Dietary Approaches to Stop Hypertension (DASH), low-glycemic diets, and caloric restriction have shown improvement in cognitive function; however, there was a negative impact on problem-solving in those with comorbid cardiovascular disease. There is also contradictory evidence that caloric restriction and diet alone may not be sufficient for the improvement of cognitive functions and that exercise may have better efficacy on cognition. Conclusion: IF is considered a safe intervention, and no adverse effects were found in the reviewed studies; however, evidence is limited as there were only 9 low-quality RCTs that assessed the impact of IF on cognition. DASH, low-glycemic diets, and exercise may have effective roles in the management and prevention of cognitive decline, although further research is needed.